Defining the Root Cause of Jakarta MBA Students’ ComplaintUsing TQM Model of Academic Excellence - Karta Negara Salam; Sri Wijaya Salam (Hasanuddin Economics and Business Review, 2019)
In the competitive world of education, many universities are competing to improve the quality of education services, employeeperformance, and produce graduates with integrity and professional skills. One of them is SBM ITB Jakarta. The purpose of thisstudy was to determine the root causes of the quality of MBA ITB Jakarta services by using a qualitative approach and “5C TQMof academic excellence” model as a guide to improve the quality of education services. While for the technique of collecting dataand analyzing qualitative data using interviews with respondents, the respondents in the study were university staff, lecturers, SBMITB Jakarta management, and students. The results of the study concluded that there absence of such a clear role from every unitinvolved (in this case, SBM ITB Jakarta staff, lecturers, and management) as the root cause of student complaints related to theservice quality of SBM ITB Jakarta. Miscommunication and misperception cannot be avoided because every unit has differentperceptions and expectations toward each other.